Association between rs20456 and rs6930913 of Kinesin-Like Family 6 and Hypertension in a Chinese Cohort - Yan-li Chen; Li-Qiang Zheng; Tie-Jun Li; Zhao-Qing Sun; Ying Hao; Bao-Gang Wu; Ying-Xian Sun (International Journal of Hypertension)
This study aimed to investigate the relationship between kinesin-like family 6 (KIF6) polymorphisms and hypertension in a northeast Chinese cohort. In this study, two single nucleotide polymorphisms of KIF6 (rs20456 and rs6930913) and their haplotype were analyzed in 382 hypertension patients and 378 controls with SHEsis analysis platform, and the gene-environmental interactions were evaluated with logistic regression analysis. After adjusting for confounding factors, significantly lower risk of hypertension was observed in participants with genotype TC (0.416 (CI 0.299–0.578), p<0.001) and CC (0.577 (0.389–0.857), p=0.007) of rs20456 compared with TT. For rs6930913, allele T (0.522 (0.386–0.704), p<0.001), genotype TT (0.325 (0.205–0.515), p<0.001), and genotype CT (0.513 (0.379–0.693), p<0.001) were significantly associated with lower risk of hypertension than allele C and CC genotype, respectively. Gene-environment analyses confirmed the significant influence on hypertension by the interactions between genotypes distribution in rs20456 (CT: p=0.036, TT: p=0.022) and smoking status. No interactions were found between smoking and rs6930913, except those with dominant or recessive genetic models (both Ps=0.006). There were no interactions between KIF6 and overweight (all Ps>0.05). Haplotype analyses showed that CC (p=0.005) and TC (p=0.001) of rs20456 and rs6930913 were significantly associated with a statistically increased risk of hypertension. The false-positive report probability (FPRP) analysis was used to verify significant findings. In conclusions, KIF6 might affect the susceptibility of hypertension. The allele C (rs20456) and allele T (rs690913) were inclined to protect individuals from hypertension both in genotype and haplotype analyses.